STRATEGY OF TREATMENT AND PROPHYLAXIS OF ATOPIC DERMATITIS - Kutasevych, Y.F. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The modern approaches to systemic and topical therapy of atopic dermatitis and scientific support for the use of classic and new medications are reviewed in this article.